Effect of a sustainable biofuel – n-octanol – on the combustion, performance and emissions of a DI diesel engine under naturally aspirated and exhaust gas recirculation (EGR) modes - Rajesh Kumar, B.; Saravanan, S.; Rana, D.; Anish, V.; Nagendran, A. (Energy conversion and management, 2016)
[Display omitted] •It is possible to operate a DI diesel engine with up to 30% n-octanol/diesel blends without modifications.•Addition of n-octanol prolonged the ignition delay, generated higher peaks of pressure and heat release rates.•Simultaneous reduction of NOx and smoke is possible under both naturally-aspirated and EGR conditions.•Engine performance improved with n-octanol addition.•HC and CO emissions decreased favorably with n-octanol addition. Higher alcohols above n-butanol can be excellent alternative fuels for diesel engines owing to their high energy content and high cetane number. The last three years has witnessed an advent of several sustainable pathways for n-octanol bio-synthesis using engineered-microbes like Escherichia coli and Clostridium species. Therefore an investigation to evaluate the compatibility of n-octanol in diesel engines becomes essential. The influence of blending n-octanol by up to 30vol% with fossil diesel on combustion, performance and emission characteristics of a single cylinder direct-injection (DI) diesel engine under both naturally aspirated and exhaust gas recirculation (EGR) modes was investigated with reference to diesel. Results showed that n-octanol prolonged the ignition delay generating higher peaks of in-cylinder pressure and heat release rates (HRR) during the pre-mixed combustion phase. Brake thermal efficiency (BTE) increased while brake specific fuel consumption (BSFC) decreased with an increase in n-octanol fraction. Smoke, NOx (nitrogen oxides), HC (hydro-carbons) and CO (carbon monoxide) emissions decreased with n-octanol addition. NOx and smoke emissions also remained low at all EGR rates. Both BTE and BSFC suffered at increased EGR rates. HC and CO emissions increased with escalating EGR rates. n-Octanol was found to be very promising for replacing fossil-diesel by up to 30% (subject to long term durability tests), in terms of emissions and performance at both naturally aspirated and EGR conditions.